2006
DOI: 10.1158/0008-5472.can-05-3013
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of hdm2 by Stress-Induced hdm2alt1 in Tumor and Nontumorigenic Cell Lines Correlating with p53 Stability

Abstract: Alternative and aberrant splicing of hdm2 occurs in tumor and normal tissues. However, the factors that induce these splice variants and whether they are translated to protein products in vivo is unknown, making it difficult to decipher which of these hdm2 transcripts have a normal physiologic function or contribute to carcinogenesis. We investigated the conditions that induce this post-transcriptional modification of hdm2 in tumor and nontumorigenic cell lines. We showed that UV and ; radiation as well as cis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…Previous studies have shown that the alternative splicing of MDM2 can be observed at UV doses from 30-50 J/m 2 over periods of 6-24 h, with variations in cell type. 49,51 Overall, these findings show that PDIP38 is required for the UV induced alternative splicing of MDM2. These findings provide evidence for a novel function of PDIP38 that may be relevant to the molecular mechanisms that may underlie the regulation of alternative splicing of MDM2.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Previous studies have shown that the alternative splicing of MDM2 can be observed at UV doses from 30-50 J/m 2 over periods of 6-24 h, with variations in cell type. 49,51 Overall, these findings show that PDIP38 is required for the UV induced alternative splicing of MDM2. These findings provide evidence for a novel function of PDIP38 that may be relevant to the molecular mechanisms that may underlie the regulation of alternative splicing of MDM2.…”
mentioning
confidence: 61%
“…29,31,32 Alternative splicing of MDM2 transcripts is induced in cultured cells by UV and genotoxic stress. 26,49,51 The appearance of the splice variants has significance beyond their impact on p53 functions, since it has been shown that the truncated MDM2 proteins may exhibit growth-regulatory properties, 29 the ability to promote tumorigenesis in mice 52 and to transform cultured cells. 32 We therefore evaluated the potential participation of PDIP38 in alternative splicing of MDM2 in response to UV irradiation.…”
mentioning
confidence: 99%
“…Strikingly, various genotoxic agents, including UV, CPT, doxorubicin and cisplatin, affect MDM2 splicing, leading to the skipping of up to 8 (out of 12) exons in MDM2 transcripts, thereby decreasing the proportion of FL-MDM2 transcripts. [35][36][37] In response to CPT, nearly all neo-synthesized MDM2 transcripts lack at least one exon. 37 This massive alteration of MDM2 splicing counteracts the strong (approximately 50-fold) transcriptional stimulation of the MDM2 gene promoter, and leads to a decrease in FL-MDM2 levels that likely contributes to protecting transcripts are degraded by NMD.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…2). [35][36][37] This is a key feature ensuring that FL-MDM2 levels only rise upon stress withdrawal, when p53 levels are still high and need to be turned off. 37 Stressinduced MDM2 splicing regulation was also observed in murine cells, further supporting its biological role.…”
mentioning
confidence: 99%
“…Treatment with DNA-damaging agents such as UV irradiation and cisplatinum induces the formation of MDM2-ALT1 transcripts (20,21). We have utilized this inducible system to develop an in vitro splicing assay using nuclear extracts from normal and cisplatinum-treated HeLa S3 cells and a damageresponsive MDM2 minigene.…”
mentioning
confidence: 99%